Arthroscopic Suture Pull-Out Fixation of Displaced Tibial Spine Avulsion Fracture - Pandey, Vivek; CPS, Suman; Acharya, Kiran; Rao, Sharath K. (The Journal of Knee Surgery, 2017)
The aim of this study is to assess the clinical and radiological outcomes of arthroscopic reduction and fixation of tibial spine avulsion in patients with either open physis or closed physis, using high strength nonabsorbable sutures utilizing intravenous cannula needle as suture passer and retriever. Twenty-six patients of mean age 24.5 years were included in the study with a mean follow-up period of 31 months. Twelve patients had McKeever type III avulsion fracture and 14 had type IV. A follow-up analysis was performed using fracture union time, range of motion assessment, and Lysholm and IKDC (International Knee Documentation Committee) scores with instrumental (KT-1000 arthrometer) laxity assessment. All avulsion fractures showed union at the end of a 3-month follow-up. Mean (± standard deviation [SD]) postoperative Lysholm and IKDC subjective scores were 97.7 (± 3.62, range, 89–100) and 95.55 (± 4.21, 82.8–100), respectively. All patients were graded IKDC grade A except one with grade B. The Lysholm score of open physis group was better than the closed physis group (99.6 vs. 96.5, p < 0.03), whereas IKDC scores of open versus closed physis group (both subjective and objective) and type III and IV McKeever groups did not reveal any statistical difference. KT-1000 assessment revealed mean (± SD) anterior translation of the tibia as 0.85 (±0.9) mm. At the final follow-up, all patients achieved complete range of movement with no symptom of instability. Two patients underwent adhesiolysis for postoperative stiffness in their knee at 4th month postoperatively. Arthroscopic suture pull-out fixation for type III and IV tibial spine avulsion results in excellent clinical and radiological outcomes in patient with open and closed physis without any significant complications. This is a prospective case series with level of evidence IV.
Keywords: knee; tibial spine; avulsion fracture; arthroscopic reduction; pull-out suture fixation